Migrant and refugee problems in Clare’s Hard Asset and their solutions - Gautam, Rajendra Prasad (Namuna Academic Journal, 2025)
The paper discusses the Rohingya refugee crisis and its implications. It highlights the need for political integration of Rohingya refugees. Humanitarian camps depoliticize refugees, limiting their agency and voice. The paper critiques the perception of Rohingyas as outsiders in Myanmar. It references Aristotle’s concept of ’barbarian’ in political exclusion. The narrative includes personal stories from the novel "Hard Asset." The paper argues for a cosmopolitan approach to refugee issues. It emphasizes the historical presence of Rohingyas in Myanmar. Statelessness leads to severe human rights crises for Rohingyas. The paper calls for solidarity cities to support refugees.